Effect of high intensity interval training on adipose tissue levels of steroid receptor RNA activator and insulin resistance index in rats with type II diabetes - Aylin Jafarzade; Najme Rezaeian (Shahid Beheshti University, 2024)
Background and Purpose: Steroid receptor RNA activator (SRA) is one of the long non-coding RNA (LncRNA) playing a dual role in glucose homeostasis and insulin resistance. Purpose of this study was to investigate the effect of six weeks of high intensity interval training on adipose tissue levels of SRA and insulin resistance index in diabetic rats with high fat diet and streptozotocin.  Materials and Methods: Twenty male wistar rats (10-12 weeks old; 200-300 gr) were selected and type 2 diabetes was induced by six weeks of high-fat diet and streptozotocin injection. Afterwards, obese diabetic rats were randomly divided into experimental and control groups. The rats in the experimental group participated in six weeks of high intensity interval training included 40 seconds of running on a treadmill at 25-35 m/min followed by 2 minutes of active rest at 10 m/min, which was performed for 30 minutes per session, five sessions per week, 6 weeks. All rats were dissected 48 hours after the last training session and adipose levels of SRA, serum levels of insulin and fasting blood sugar were evaluated using appropriate laboratory methods. Data analyses were carried out using independent and paired t-test and Pearson's correlation test at a significance level of less than 0.05. Results: Six weeks of high intensity interval training resulted in significant decreases in adipose tissue levels of Steroid Receptor RNA Activator (P=0.001) in addition to significant decreases in levels of insulin (P<0.001), fasting blood glucose (P<0.001), insulin resistance index (P<0.001) and body weight (P=0.028) in the experimental group compared to the control group. Furthermore, six weeks of high intensity interval training in experimental group caused significant decreases in body weight in post- test compared to pre- test (P<0.001). However, according to the Pearson's correlation test, there were no significant correlations between the changes in steroid receptor RNA activator levels of adipose tissue and changes in other variables following high intensity interval training (P>0.05) Conclusion: It seems that in addition to improving body composition, six weeks of high intensity interval training play a role in improving insulin resistance through decreasing the levels of SRA.